Desain Gas Lift Dengan Metode Continuous Flow Untuk Mendapatkan Laju Alir Optimal Pada Sumur “F-1” Lapangan “X” - Dimas Putra Wibowo; M. Nur Mukmin; Rohima Sera Afifah; R.Bambang Wicaksono; Amiruddin; Luthfiyah Atisa Fadhilah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2021)
Well kick is the entry of formation fluid into the drill hole which causes formation pressure greater than the hydrostatic pressure of the drilling mud. The purpose of this study is to find out what factors cause a kick to occur, and how to repeat the kick using the wait and weight method. The wait and weight method is a kick countermeasures method with one circulation by new heavy mud. Steps to counteract well kick in the